2001
DOI: 10.1046/j.1439-0280.2001.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of development of Callosobruchus maculatus (F.) (Col.: Bruchidae) in bambara groundnut seeds exposed to solar heat in the Nigerian savanna

Abstract: The effect of solarization on the development of Callosobruchus maculatus was investigated in the Nigerian savanna during the hot season from April to May, 1999. Development of C. maculatus adult progeny was completely suppressed in seeds of bambara groundnut, Vigna subterranea bearing bruchid eggs or harbouring first and second instar larvae that were exposed to the sun in metal tins, clay pots or polypropylene sacks for 7, 14 or 28 h. Adults of C. maculatus developed only in seeds that were not exposed to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Overall, we observed some sort of increase in mortality of cowpea bruchid eggs and decrease in adult emergence with an increase in exposure time of solar heat treatment as indicated by the correlation and regression analyses. This is in consonance with earlier reports by Lale and Ajayi (2001) and Lale and Vidal (2003) who studied the effect of solarization on egg mortality and progeny emergence of C. maculatus and showed that; solar heat treatment of cowpea seeds can adequately control infestation by cowpea seed bruchids. It has been shown that exposing infested cowpea grains to a temperature of 57 0 C for 1 h in an oven kills all the immature stages (eggs, larvae and pupae) of C. maculatus within the seeds -this temperature per exposure time was thus reported as the thermal death point of C. maculatus (Murdock and Shade 1991).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, we observed some sort of increase in mortality of cowpea bruchid eggs and decrease in adult emergence with an increase in exposure time of solar heat treatment as indicated by the correlation and regression analyses. This is in consonance with earlier reports by Lale and Ajayi (2001) and Lale and Vidal (2003) who studied the effect of solarization on egg mortality and progeny emergence of C. maculatus and showed that; solar heat treatment of cowpea seeds can adequately control infestation by cowpea seed bruchids. It has been shown that exposing infested cowpea grains to a temperature of 57 0 C for 1 h in an oven kills all the immature stages (eggs, larvae and pupae) of C. maculatus within the seeds -this temperature per exposure time was thus reported as the thermal death point of C. maculatus (Murdock and Shade 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Post-harvest losses of up to 90% due to heavy infestation by C. maculatus on stored cowpea have been reported (Radha and Susheela 2014). The infested cowpea seeds become less desirable for human consumption and most times are not used for seeds and market purposes as a result of insect eggs and exit holes appearance on seeds (Lale and Ajayi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These results were similar to the findings of Mekasha (2004) who reported that exposure to solar heat for 75 and 90 minutes significantly affected seed viability of adzuki bean. In contrast, Lale and Ajayi (2001) found that solarization in metal tins for 7 hours with temperatures of up to 57 °C had no significant adverse effect on germinability of bambara groundnut seeds.…”
Section: Effect Of Solar Heater Boxes On Seed Quality Of Adzuki Bean mentioning
confidence: 82%
“…Insects (mainly stored grain pests) have been controlled by soil solarization to some extent as well. Soil solarization was observed to change soil chemistry which may weaken or kill some kinds of soil organisms ( McFarlane, 1989 ; Elmore et al, 1997 ; Lale and Ajayi, 2001 ; Minarro and Dapena, 2003 ; Gill and McSorley, 2010 ; Summers et al, 2010 ).…”
Section: Soil Solarization: a Brief Compendiummentioning
confidence: 99%